Characterization and Evolution of the Spotted Gar Retina. Issue 7 (9th November 2016) - Sukeena, Joshua M.; Galicia, Carlos A.; Wilson, Jacob D.; McGinn, Tim; Boughman, Janette W.; Robison, Barrie D.; Postlethwait, John H.; Braasch, Ingo; Stenkamp, Deborah L.; Fuerst, Peter G.
ABSTRACT: In this study, we characterize the retina of the spotted gar, Lepisosteus oculatus, a ray‐finned fish. Gar did not undergo the whole genome duplication event that occurred at the base of the teleost fish lineage, which includes the model species zebrafish and medaka. The divergence of gars from the teleost lineage and the availability of a high‐quality genome sequence make it a uniquely useful species to understand how genome duplication sculpted features of the teleost visual system, including photoreceptor diversity. We developed reagents to characterize the cellular organization of the spotted gar retina, including representative markers for all major classes of retinal neurons and Müller glia. We report that the gar has a preponderance of predicted short‐wavelength shifted (SWS) opsin genes, including a duplicated set of SWS1 (ultraviolet) sensitive opsin encoding genes, a SWS2 (blue) opsin encoding gene, and two rod opsin encoding genes, all of which were expressed in retinal photoreceptors. We also report that gar SWS1 cones lack the geometric organization of photoreceptors observed in teleost fish species, consistent with the crystalline photoreceptor mosaic being a teleost innovation. Of note the spotted gar expresses both exo‐rhodopsin (RH1‐1) and rhodopsin (RH1‐2) in rods. Exo‐rhodopsin is an opsin that is not expressed in the retina of zebrafish and other teleosts, but rather is expressed in regions of the brain. This study suggests that exo‐rhodopsin is an ancestral actinopterygian (ray finned fish) retinal opsin, and in teleosts its expression has possibly been subfunctionalized to the pineal gland.